(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This work applies the Modified Optimal Homotopy Asymptotic Method (MOHAM) to two benchmark singular two–point boundary value problems that were previously analyzed using the standard OHAM. The modification introduces a refined homotopy framework in which nonlinear and singular terms are systematically distributed across successive embedding orders, while the auxiliary function is optimally tuned through residual minimization. With this enhancement, MOHAM delivers first–order analytical approximations that are nearly identical to the exact solutions, achieving higher accuracy, faster convergence, and greater computational efficiency than the conventional OHAM even when the latter is extended to three terms of approximation